Service orientation in holonic and multi-agent manufacturing control - Thomas, Andre; Trentesaux, Damien; Borangiu, Theodor (Studies in Computational Intelligence,, 2012)
Service orientation is emerging nowadays at multiple organizational levels in enterprise business, and it leverages technology in response to the growing need for greater business integration, flexibility and agility of manufacturing enterprises. This book gathers contributions from scientists, researchers and industrialists on concepts, methods, frameworks and implementing issues addressing trends in the service orientation of control technology and management applied to manufacturing enterprise. It analyzes a Service Oriented Architecture (SOA) representing a technical architecture, a business modelling concept, a type of infrastructure, an integration source and a new way of viewing units of automation within the enterprise. The presents how SOA aligns the business world with the world of information technology in a way that makes both more effective.